Value systems of representatives of different generations in the process of decision-making on choosing a university and educational program - O. I. Popova; G. S. Timokhina; N. B. Izakova (Модернизация, инновация, развитие, 2023)
Purpose: is to propose the methodological approach to modeling the behavior of the representatives of generations Y and Z in the process of making decisions about choosing a university and educational program based on differences in their value systems.Methods: the theoretical and methodological basis for studying the value systems of potential and actual university students is the theory of generations. The findings of the study are based on the methods of analysis of secondary and primary data collected through an online survey of students belonging to generations Y and Z on representative samples of 380 (Y) and 788 (Z) observations in 20 large universities in Russia, as well as the methods of analysis of statistically significant differences in value systems of two generations using T-test for independent samples.Results: the authors proposed the methodological approach to modeling the behavior of consumers of generations Y and Z in the process of making decisions on choosing a university and educational program. Based on the results of desk and field (empirical) research, at each stage of the decision-making process on selecting an educational institution and program, differences were identified in the value systems of students of generations Y and Z, which determine their behavior: statistically significant differences were identified in 19 out of 65 variables. The study provides description of the behavior patterns of students of the two generations at each stage of the decision-making process which formed the basis for dividing students into target groups. The guidelines for differentiating marketing interactions with target groups of representatives of two generations in the process of educational interactions while making decisions are proposed.Conclusions and Relevance: differences in the value systems of representatives of generations Y and Z cause differences in behavioral patterns at each stage of the decision-making process. Understanding these differences enables us to model the behavior of the two target groups, differentiate marketing approaches to interaction with them at the stages of the decision-making process while choosing a university and educational program as well as increase the effectiveness of educational interactions in the process of education.